Navien catheter experience in neuroendovascular interventions. Issue 5 (October 2017) - Jindal, Gaurav; Giacon, Luciano; Iyoha, Moronke; Miller, Timothy; Aldrich, Francois; Simard, Marc; Shivashankar, Ravishankar; Gandhi, Dheeraj
Purpose: Advancements in catheter technology have allowed for greater flexibility and trackability. We report 265 consecutive, single-center neurointerventional cases using the Navien guide catheter. Materials and methods: Retrospective analysis was performed of consecutive intracranial endovascular procedures utilizing the Navien catheter. Data collected included procedure type, catheters, guide catheter position, cervical access artery tortuosity grade and complications. Results: The 5 French catheter was used in 130 cases. The 6 French catheter was used in 135 cases. Access was via the internal carotid artery in 204, external carotid artery in 10, and vertebral artery in 51 cases. Catheter tip position was in the petrous segment of the internal carotid artery in 36.6% (97/265), distal cervical internal carotid artery in 13.9% (37/265), cavernous internal carotid artery in 10.2% (27/265), proximal or mid cervical internal carotid artery in 5.6% (15/265), supraclinoid internal carotid artery in 0.8% (2/265), and intradural vertebral artery in 0.8% (2/265) of cases. Catheter position was not determined in 18.9% (50/265) of cases. Proximal vessel tortuosity (grade B or C) was present in 98 cases (37%), and the catheter was tracked distal to the tortuosity in 93% (91/98) of these cases. The overall success rate without catheter complication was 97% (258/265). The Navien was replaced by another catheter in 1.9% (5/265) of cases. There was one cervical artery dissection (0.4%) and one severe vasospasm (0.4%) necessitating Navien removal. Conclusions: The Navien guide catheter provided distal access support for neuroendovascular interventions in nearly all cases, including cases with proximal artery tortuosity, with a low rate of catheter-related complications.